Expansão de Homo sapiens e extinção da megafauna na América do Sul: como os efeitos antrópicos e climáticos influenciaram na extinção dos proboscídeos - Oliveira, Hauanny Rodrigues (2020)
Understanding the process of Homo sapiens expansion in the Americas, especially in South America, is still complex and there is no consensus on several aspects such as the date of arrival, the routes followed by the first populations, the number of waves of colonization, where they arrived and the origin of these first populations. However, we know that the expansion of humans across the planet influenced the extinction of the megafauna in the Late Quaternary, mainly large mammals (over 45 kg), with South America being one of the continents with the greatest loss of species (~ 80%). In this context, the objective of the thesis was to explore, through ecological models, the human expansion processes in South America and their effects on the extinction of Proboscideans in that continent. In the first chapter, we developed an ecological model that simulates the expansion of H. sapiens in order to map the time of expansion and abundance of H. sapiens from 21 thousand years ago to the present. In chapter 2, using the ecological niche model, we obtained the environmental suitability and the range for the South American Proboscideans throughout the continent and in various periods, with the main objective of understanding if the effect of the climate change influenced the extinction of these species. In the third chapter, we apply a basic demographic model that simulates predator-prey dynamics, considering that H. sapiens hunted megafauna, together with variables that take into account climate change, in order to understand whether the joint effects of hunting and climate change influenced the extinction of Proboscideans in South America. Our results showed that in less than 500 years after the arrival of H. sapiens, the entire continent was already colonized and the places with greater support capacity showed greater abundance. The effects of climate change alone were not able to extinguish the Proboscideans, because in periods when these species were already extinct there were still habitats suitable for their survival. However, the joint effects of hunting by humans and climate change influenced the extinction of Proboscideans, showing that the arrival of H. sapiens really affected the survival of the megafauna, which had already overcome several climatic fluctuations throughout the Quaternary period.